Human Ethics as the Basis of Religious Moderation: A Reflection on Character Education Practices at Pondok Al Fithrah Surabaya - Fathur Rozi; Siti Aisyah (Mahad Aly Al Fithrah, 2026)
This article examines the role of human ethics as a foundation for fostering religious moderation, with a particular focus on character education practices at Pondok Al Fithrah Surabaya. In the contemporary era, where religious polarization and intolerance remain pressing challenges, pesantren institutions play a crucial role in nurturing balanced and inclusive perspectives among young Muslims. Human ethics, understood as universal values such as justice, compassion, tolerance, and respect for human dignity, provides an essential framework for developing a moderate religious attitude rooted in Islamic spirituality. The study employs a qualitative-descriptive approach, drawing on observations, interviews with educators and students, and document analysis at Pondok Al Fithrah. Findings suggest that the pesantren integrates human ethics into daily practices, including the cultivation of humility, discipline, cooperation, and respect for diversity in religious and social life. These values are embedded not only in the formal curriculum but also in extracurricular activities, communal rituals, and the living tradition of Sufi-oriented education. Moreover, the article highlights how Al Fithrah’s approach contributes to the broader discourse of religious moderation in Indonesia by promoting harmony, preventing radical tendencies, and encouraging constructive engagement with plural society. It concludes that the integration of human ethics in character education at pesantren serves as a practical model for shaping moderate, ethical, and socially responsible individuals, thereby reinforcing the role of Islamic boarding schools as vital agents of peacebuilding and moral development in the 21st century.